2018
DOI: 10.1002/jctb.5679
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐containing wastewater treatment by photo‐assisted wet peroxidation using Au nanosized catalysts

Abstract: Background The aim of this study is to test different supports on which to deposit Au nanoparticles and to determine the most suitable for Orange II (OII) dye degradation by a photo‐assisted wet peroxidation (PWPO) process. The catalysts used (Au‐Fe2O3, Au‐TiO2, Au‐ZnO and Au‐Al2O3) were prepared by the deposition–precipitation method; a reference catalyst from the World Gold Council, hereafter denoted as Au‐Fe2O3*, was also used for comparison. The catalysts were characterized in terms of surface area (SBET),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…98% and 47%, respectively, consumption of H 2 O 2~9 6%, and higher hydroxyl radicals generation) and the highest TOF value for OII dye removal (75.5 × 10 −6 s −1 ).The best efficiency of CPWO for Au/Al 2 O 3 was associated to its higher adsorption capacity. The same was concluded for these same catalysts when light-assisted CWPO was used for OII dye degradation [110]. Au/Al 2 O 3 permitted total discoloration and TOC removal of about 80%, combining further formation of hydroxyl radicals [110].…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…98% and 47%, respectively, consumption of H 2 O 2~9 6%, and higher hydroxyl radicals generation) and the highest TOF value for OII dye removal (75.5 × 10 −6 s −1 ).The best efficiency of CPWO for Au/Al 2 O 3 was associated to its higher adsorption capacity. The same was concluded for these same catalysts when light-assisted CWPO was used for OII dye degradation [110]. Au/Al 2 O 3 permitted total discoloration and TOC removal of about 80%, combining further formation of hydroxyl radicals [110].…”
mentioning
confidence: 53%
“…The same was concluded for these same catalysts when light-assisted CWPO was used for OII dye degradation [110]. Au/Al 2 O 3 permitted total discoloration and TOC removal of about 80%, combining further formation of hydroxyl radicals [110]. In the same way, Drašinac et al [107] observed that the morphological properties of the catalysts and gold properties played an important role in methyl orange (MO) dye degradation.…”
mentioning
confidence: 61%
See 3 more Smart Citations